A model for predicting ground reaction force and energetics of human locomotion with an elastically suspended backpack. Issue 14 (26th October 2022) - Huang, Ledeng; Yang, Zhenhua; Wang, Ruishi; Xie, Longhan
Abstract: This paper presents an actuated spring-loaded inverted pendulum model with a vertically constrained suspended load mass to predict the vertical GRF and energetics of walking and running. Experiments were performed to validate the model prediction accuracy of vertical GRF. The average correlation coefficient was greater than 0.97 during walking and 0.98 during running. The model's predictions of energy cost reduction were compared with experimental data from the literature, and the difference between the experimental and predicted results was less than 7%. The predicted results of characteristic forces and energy cost under different suspension stiffness and damping conditions showed a tradeoff when selecting the suspension parameters of elastically suspended backpacks.